Complex neuroimaging study of the proximal segment after rigid fixation and dynamic stabilization in patients with degenerative lumbar disease - A. E. Krivosсhein; S. V. Kolesov; A. A. Kalinin; V. P. Konev; A. I. Kazmin; S. N. Moskovskiy; V. A. Byvaltsev (Acta Biomedica Scientifica, 2023)
Background. The development of the adjacent level syndrome and, as a consequence, adjacent segment degenerative disease are currently the most common complications of decompression and stabilization surgery with the development of segmental instability.The aim of the study. To conduct a comprehensive neuroimaging assessment of  the proximal adjacent segment after rigid fixation and dynamic stabilization in degenerative lumbar disease.Materials and methods. We conducted a prospective multicenter study of the results of surgical treatment of 274 patients with degenerative-dystrophic diseases of the lumbar spine, who underwent monosegmental decompression and stabilization surgery using the TLIF (transforaminal lumbar interbody fusion) technique and open transpedicular rigid fixation, as well as open hemilaminectomy with stabilization of the operated segments with nitinol rods. The study included radiography, diffusion-weighted magnetic resonance imaging and computed tomography (dualenergy mode) of intervertebral discs and isolated facet degeneration of the upper adjacent level.Results and discussion. Combination of the initial proximal segment degeneration in the form of  facet joints degeneration (density of cartilaginous plate  – 163.5 ± 14.2 HU, density of external facet – 709.35 ± 13.6 HU, density of internal facet – 578.1  ±  12.1  HU), Pfirrmann III, IV  grade degeneration of intervertebral disc and a measured diffusion coefficient of less than 1300 mm2/s cause high risks of developing adjacent segment degenerative disease, which regulates the use of monosegmental dynamic fixation with nitinol rods, or preventive rigid fixation of the adjacent segment.Conclusion. Using complex neuroimaging in the preoperative period makes it possible to predict the results of surgical treatment, take timely measures to prevent degenerative diseases of the adjacent segment, and to carry out dynamic monitoring of processes in the structures of the spinal motion segment.